On a new species of cavernicolous crab of the genus Sesarmoides Serene & Soh, 1970 (Crustacea: Decapoda: Brachyura: Sesarmidae) from Sulawesi, Indonesia - Naruse, T. (2014)
Raffles Bulletin of Zoology